2016
DOI: 10.1002/app.43841
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and studies on core–shell type anion exchange resins based on a hybrid polymeric support

Abstract: In pursuit for new materials for recovery of noble metals, novel anion exchangers, based on new type of core-shell polymeric supports have been synthesized. The designed matrices, with reactive chloromethyl groups concentrated on a surface of the polymeric base, the Amberlite XAD-4 adsorbent, have been modified using ethylenediamine and polyethyleneimine. The obtained ion exchangers were employed in processes of sorption of gold, platinum, and palladium chlorocomplexes, then, they were compared to similar resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Nevertheless, because the reaction mixture still contained the unreacted precursor, excess NaOH was introduced into the mixture to prevent the formation of HCl. As time passed, the remaining AuCl 4 − ions must eventually be exchanged due to its strong affinity towards amino groups [ 29 , 30 , 31 ]. However, because of the earlier reaction, only water is generated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, because the reaction mixture still contained the unreacted precursor, excess NaOH was introduced into the mixture to prevent the formation of HCl. As time passed, the remaining AuCl 4 − ions must eventually be exchanged due to its strong affinity towards amino groups [ 29 , 30 , 31 ]. However, because of the earlier reaction, only water is generated.…”
Section: Resultsmentioning
confidence: 99%
“…For example, previous works demonstrated that the presence of quaternary ammonium groups in a polymer improves the stabilizing abilities of nanocomposites [ 28 ]. The application of amino-ligands that have an affinity towards Au species [ 29 , 30 , 31 , 32 ] also cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…As the result, the anion exchange resin was not only resistant to aqua regia but also allowed to receive 100% recovery of Au from WEEE. reduce the time of the adsorption process [40]. What is more, selectivity of the resin was ensured by incorporation of 1-(2-aminoethyl)piperazine, revealing a strong affinity toward Au(III) [26,41].…”
Section: Conversion Of Monomersmentioning
confidence: 99%
“…The synthetic protocol, as displayed in Figure 3, involved impregnation of highly crosslinked macroporous Amberlite XAD-4 adsorbent with VBC and DVB monomers further polymerized to create a layer of VBC-co-DVB copolymer functionalized in the next step, using aliphatic and heterocyclic amines. Crosslinked polymeric base (XAD-4) ensured chemical stability of the material, while the localization of the functionalities in its outer layer allowed us to reduce the time of the adsorption process [40]. What is more, selectivity of the resin was ensured by incorporation of 1-(2-aminoethyl)piperazine, revealing a strong affinity toward Au(III) [26,41].…”
Section: Conversion Of Monomersmentioning
confidence: 99%